Automatic Illumination‐Invariant Image‐to‐Geometry Registration in Outdoor Environments. (14th June 2017) - Kehl, Christian; Buckley, Simon J.; Viseur, Sophie; Gawthorpe, Robert L.; Howell, John A.
Abstract: Image‐to‐geometry registration is the basis of many applications for texturing and interpreting 3D surface models. Feature‐based matching is an established, automatic approach which creates 2D–3D correspondences based on salient points and their radiometric neighbourhood. This paper presents an experimental approach for assessing the accuracy of several matching algorithms in challenging imaging environments that are subject to significant outdoor illumination variations. Furthermore, a collection of accuracy assessment metrics and quality heuristics emerge from the presented approach to guide a user during the examination of registration results. As a result of the experiments, two novel salient point descriptor matching combinations outperform the standard scale‐invariant feature transform (SIFT) operator on the task of image‐to‐image and image‐to‐geometry registration under varying illumination conditions.